Corporate Social Responsibility and Business Value of Multinational Companies: Lessons from a Sub-Saharan African Environment - Abugre, J.B.; Anlesinya, A. (Journal of African Business, 2019)
The issue of corporate social responsibility (CSR) as an approach for businesses to independently take actions that lead to better levels of societal development as well as higher value creation for the business, particularly in developing countries has gained much advocacy. Thus, the purpose of this study is to examine the relationship between CSR and business value of multinational companies (MNCs) in sub-Saharan Africa. The study adopted quantitative research methodology and using multiple regression analysis, findings show that CSR can positively and significantly predict business values in the multinational subsidiaries. These values include direct (economic value) and indirect (human capital value and reputational business value). This paper therefore contributes to a novel CSR index from the perspective of business value and sustainability of MNCs in the Sub-Saharan Africa (SSA) environment. Thus, the paper recommends MNCs operating in Africa to enhance their social investment through their CSR strategy with the aim that CSR must not be regarded as a cost center, but an investment instrument that can accrue various dividends.
Keywords: CSR; Corporate reputation; Economic value; Human capital value; Multinational companies; Sub-Saharan Africa; Ghana